1984
DOI: 10.1002/ajmg.1320180208
|View full text |Cite
|
Sign up to set email alerts
|

Multiple synostosis syndrome: Study of a large Brazilian kindred

Abstract: We report a large Brazilian kindred with 28 cases of the autosomal dominant multiple synostosis syndrome. The main anomalies were symphalangism and carpal and tarsal synostoses. Other common findings included synostosis involving other bones, absence of phalanges and nails, short metacarpals, pes planovalgus with prominent lateral border, hypoplastic alae of nose, short upper lip, and dermatoglyphic abnormalities. This may be a variant of the WL syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Mutations leading to increased BMP14 (also known as GDF5 for growth differentiation factor) (Da-Silva et al, 1984) signaling may cause SYM1 or SYNS1 (Lehmann et al, 2007), and are not associated with hearing loss (Potti et al, 2011). Expression of BMP14 was recognized in the annular stapedial ligament, and absence of BMP14 expression in the middle ear ossicles was suggested to lead to failure of inossicular joint formation (Hwang and Wu, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mutations leading to increased BMP14 (also known as GDF5 for growth differentiation factor) (Da-Silva et al, 1984) signaling may cause SYM1 or SYNS1 (Lehmann et al, 2007), and are not associated with hearing loss (Potti et al, 2011). Expression of BMP14 was recognized in the annular stapedial ligament, and absence of BMP14 expression in the middle ear ossicles was suggested to lead to failure of inossicular joint formation (Hwang and Wu, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…These syndromes were first reported by Cushing (Cushing, 1915) and Vesell (Vessel, 1960). In 1990, similar overlapping clinical syndromes were recognized as stapes ankylosis with broad thumbs and toes (SABTT), which is also known as TeunisseneCremer syndrome (Teunissen and Cremers, 1990), proximal symphalangism (SYM1) (Hurvitz et al, 1985), multiple synostoses syndrome 1(SYNS1) (Da-Silva et al, 1984), tarsal-carpal coalition syndrome (TCC) and brachydactyly type B2 (BDB2). These syndromes were thought to be non-identical at first, but direct sequence analysis of genes showed that mutations in NOG induce these syndromes, which are typical phenotypes of NOG mutations.…”
Section: Introductionmentioning
confidence: 96%
“…SYM1, SYNS1, and SYNS2 syndromes are characterized by multiple joint fusions that are restricted to proximal interphalangeal joints of the hands and feet and carpal and tarsal bones; SYNS1 and SYNS2 patients additionally display multiple joint fusions in vertebrae and the hip (da-Silva et al 1984;Gaal et al 1987;Gong et al 1999;Takahashi et al 2001;Mangino et al 2002). SYM1 is caused by gain-of-function mutations in GDF5 that strongly increase ligand affinity for the BMPRIA receptor and result in loss of binding specificity for BMPRIB (Nickel et al 2005;Seemann et al 2005).…”
Section: Digit Malformations Caused By Disruption Of Tgf-b and Bmp Simentioning
confidence: 99%
“…In this type of symphalangism, synostosis appears in multiple joints. For this reason, some authors stated that this type of symphalangism should be included in the entity of multiple synostosis (Maroteaux et al, 1972;Nixon, 1978;da-Silva et al, 1984).…”
Section: Discussionmentioning
confidence: 99%